'My IT vendor does not love me anymore!': How does an organisation benefit from an effective IT vendor management strategy?...and why are some vendor relationships more successful than others? - Miller, Simon Thomas (2007)
This dissertation examines IT vendor management and the way relationships between customers and IT vendors are managed in organisations. Effective Vendor Management is learning how to optimise the resources and services paid for by an organisation so as to meet the demands of the enterprise. This definition emerged from examining the literature in which two approaches to IT vendor management were identified: risk and learning. The literature also revealed that many organisations have problems with vendor management and are not satisfied with their own practices. One survey highlights that most organisations build their vendor management skills through trial and error. This reinforces the view that vendor management is based on more or less effective methods of organisational learning. Most of the literature in vendor management is non-academic, originating from professional magazines and newspapers. The challenge for this management project was to find common issues that could be used to bring further understanding as to why some organisations were more successful in vendor management than others. Six main organisational benefits were identified across literature for an effective IT vendor management strategy. These benefits could be used to examine which cases had an effective vendor management strategy. Case studies were considered the best approach for a research strategy because they help explain the real-life experiences of organisations that are too complex for survey or experimental strategies. The research strategy is based on recommendations by Yin (2003) in his book on case study research. To begin a general analysis of vendor management, the challenge was to firstly identify various strategies across literature and categorise them in order to see how organisations did vendor management differently. It was found that organisations differed in their strategic approach to vendor management in two extreme ways. It emerged that some organisations used managed co-operation and others managed competition with vendors. This helped in recognising and selecting case studies for validation of general propositions. These general propositions were used to direct examination on three common issues that needed to be addressed in order to achieve 'Total Vendor Management'. A number of other articles and authors across literature were used to assess and verify the significance of these issues from the following categories: relationship management, managed acquisition of vendor solutions and governance. The relationship management category had the highest number of articles and authors, followed by managed acquisition, then governance which had the lowest. Each general proposition was tested using multiple cases of organisations involved in managing IT vendor relationships. The cases provided replication of successes and examples of failure to validate the propositions. The general propositions were then evaluated by looking at rival theories and modified to create the final propositions: